Incorporation of dietary nitrogen from fish meal and pea meal (Pisum sativum) in muscle tissue of Pacific white shrimp (Litopenaeus vannamei) fed low protein compound diets - Martínez Rocha, Luis; Gamboa Delgado, Julián; Nieto López, Martha Guadalupe; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth (Wiley, 2013)
Stable isotope analyses were applied to explore the relative dietary nitrogen contributions from fish meal and pea meal (Pisum sativum) to muscle tissue of Pacific white shrimp postlarvae (141 ± 31 mg) fed low protein diets having different proportions of both ingredients as the sole dietary protein sources. A negative control diet was formulated to contain 100% pea meal and six more isoproteic diets to have decreasing levels of pea meal-derived nitrogen: 95, 85, 70, 55, 40 and 0 % of the initial level. Growth rates were negatively correlated to dietary pea protein inclusion due to progressive essential amino acid deficiencies (sulfur amino acids, threonine, lysine, histidine). The nitrogen turnover rate significantly increased in muscle tissue of shrimps fed diets having high levels of pea meal; however, contrary to observations from a previous study using soy protein , the relative contributions of dietary nitrogen from pea meal to shrimp muscle tissue were equal or higher than expected contributions established by the dietary formulations. Results highlight the effectiveness of stable isotope analysis in assessing the nutritional contributions of alternative ingredients for aquaculture feeds and the potential suitability of pea as a source of protein (provided the diets are nutritionally balanced).